The general practitioner's use and expectations of an accident and emergency department. - Morrison, W G (1990)
In an attempt to establish what the general practitioner expects from an accident and emergency department, and how closely the service provided correlates with that view, a 12-point questionnaire was sent to the general practitioners in the Glasgow Royal Infirmary catchment area. Out of the 61.2% of general practitioners who replied, the majority wish to have responsibility for their own patients for conditions which are neither accidents nor emergencies. There is less agreement as to how much should be done within an accident and emergency department and on the appropriate modes of referral and communication between the general practitioner and the hospital service. Further consultation and cooperation are necessary to interpret and resolve these differences.